The Potential Application of Giant Reed (Arundo donax) in Ecological Remediation - Zhang, Deng; Jiang, QianWen; Liang, DanYang; Huang, Shixun; Liao, Jianxiong (Frontiers in Environmental Science, 2021)
With the continuously growing industry around the world, environmental pollution becomes a severe issue, which will cause a potential impact on human health. As a multi-use plant, Giant reed has not only significant economic benefit but also sound ecology and social benefit in heavy metal contaminated soil remediation. Because of its high biomass yield, adaptation to different types of soils and weather conditions, lower tillage requirement than traditional economic trees, giant reed has been widely planted and used for artificial board and paper production. Mainly, giant reed is a promising tool for phytoremediation, and this plant shows strong growth capability in different soils with wide ranges of pH, salinity and high heavy metal contents. Importantly, as the toxic elements are not accumulated in aerial biomass (shoots), giant reed can be used for bioenergy or biopolymer production. In contrast, underground biomass (rhizomes) earned toxic elements so that it can be harvested and removed from the soil. Here, we review the available evidence regarding the utilization of giant reed in the field of phytoremediation and discuss the potential application of giant reed combined with advanced remediation technologies in ecological remediation.